The Wisdom-Based Thinking and its Relationship to the Psychological Capital: طلل غالب علوان (Journal of the College of Education for Women, 2021)
The present study aims to identify wisdom-based thinking and its relationship to psychological capital. It further aims to find out the differences in the level of wisdom-based thinking and psychological capital according to the variables of gender and specialization (scientific, humanities). To achieve this, the study has been conducted on a sample of (380) male and female students. The two scales, wisdom-based thinking and psychological capital are implemented to the sample after being constructed by the researcher and after ensuring their psychometric characteristics' suitability for the study's aims. Results concerning the first aim have shown that there is a significant relationship among students. The second aim has revealed that there is no statistically significant difference according to the gender variable in wisdom-based thinking. According to the variable of specialization in wisdom-based thinking, there are statistically significant differences. Besides, there is no statistically significant difference between the variables of gender and specialization in wisdom-based thinking. According to the third aim, the results have proven a significant relationship among students, whereas the fourth aim does not have any statistically significant differences according to the gender variable. There are statistically significant differences in favor of students of humanities specialization. It has further found that there are statistically significant differences between the gender and specialization variables. Further, in the fifth aim, results have shown that there is a significant correlated relationship between the two variables. Accordingly, the study has set forward a number of recommendations and suggestions.